TAP, HLA-DQB1, and HLA-DRB1 polymorphism in Colombian patients with primary Sjögren's syndrome (2002)
Objective: Although primary Sjögren's syndrome (pSS) has a worldwide distribution, little data is available on pSS immunogenetics in non-white populations. Thus, we investigated the influence of transporters associated with antigen processing (TAP), human leukocyte antigen (HLA)-DQB1, and HLA-DRB1 gene polymorphism in mestizo Colombian patients with pSS. Methods: In this cross-sectional and controlled study, all patients met the European criteria for classification of pSS. TAP and HLA typing was performed by polymerase chain reaction techniques. Genetic data analysis was performed to detect deviations from the expected Hardy-Weinberg (H-W) proportions and to determine the presence of population stratification or subdivision and the existence of linkage disequilibrium between pairs of loci. Results: Seventy-three Colombian patients with pSS (95% women) and 76 healthy controls were studied. Although significant associations were not observed between TAP or HLA polymorphism and disease, strong linkage disequilibrium among the loci TAP2 and DQB1 was found in patients. Deviations from the H-W expected value were found in the DQB1 locus of patients (P =.02). HLA-DRB1*0301-DQB1*0201 haplotype was associated with more severe histopathologic disease (odds ratio [OR], 15.5; 95% confidence interval [CI], 1.9-129; P =.001) and the presence of anti-Ro (OR, 3.8; 95% CI, 1-15; P =.04) and anti-La antibodies (OR, 4.3; 95% CI, 1.3-14; P =.01). Conclusion: The data show genetic evidence suggesting that, in Colombians, a region immersed or in the vicinity in the HLA class II system is strongly associated with a predisposition to acquire pSS, which is probably located between the TAP2 and HLA-DQB1 locus. Our results confirm that the HLA-DRB1*0301-DQB1*0201 haplotype participates in the pathogenesis of pSS.